METHODOLOGICAL FRAMEWORK FOR STUDYING PULMONARY MORPHOLOGICAL RESPONSES TO FOOD INDUSTRY DYES AND PHYTOTHERAPEUTIC INTERVENTION. (International journal of artificial intelligence, 2026)
The food industry actively uses various types of dyes, classified as synthetic and natural. Synthetic dyes, which are artificially created organic compounds, are not usually found in the natural environment. Their production is often carried out in the form of granules or powders, which are easily dissolved in an aqueous environment .Unlike synthetic dyes, natural dyes are made exclusively from natural sources. These natural substances not only color foods, but also enrich them with biologically active elements and nutrients, increasing their nutritional value. However, natural dyes are susceptible to deterioration under the influence of high temperatures and air, which requires manufacturers to pay special attention to their storage conditions.The problem of using food dyes in nanoforms, such as titanium dioxide (E171), iron oxides (E172), as well as metallic dyes based on silver (E174) and gold (E175), is becoming increasingly relevant and requires additional study. Nanoparticles have properties that can differ significantly from the properties of larger particles of the same substances, which creates the need for an in-depth analysis of their impact on human health .In Uzbekistan, as well as at the international level, accepted methods for controlling the quality and safety of food coloring additives must meet standards that ensure the reliability of research results.